Liver transplantation for metastatic neuroendocrine tumors - Barbier, Louise (Hepat Oncol, 2014)
Neuroendocrine tumors are a heterogeneous group of rare epithelial tumors. Most of them are metastatic at the time of initial diagnosis. Liver transplantation (LT) has been proposed in selected patients with diffuse liver involvement. Rationale for LT in this indication is based on the frequently indolent nature of neuroendocrine tumors, the propensity for liver-only metastasis and the high rate of intrahepatic recurrence after resection. However, indications for LT for neuroendocrine liver metastases remain controversial, and patient selection criteria is still a matter of debate. The aim of this review is to summarize data regarding LT for neuroendocrine liver metastases by answering frequently asked questions about this issue.